Comparison of two kiln-drying schedules for turkish hazel (Corylus colurna) lumber of 5-cm thickness - Süleyman KORKUT; Nusreta AS; Ümit BÜYÜKSARI (Maderas: Ciencia y Tecnología, 2018)
Turkish hazel (Corylus colurna) lumber with a nominal thickness of 5 cm from the Kastamonu region, Turkey, was dried through conventional kiln drying using two different programs, a non-protective drying schedule and a protective drying schedule. The goal of the study was to obtain a kiln schedule that would maintain wood quality and also save drying time until a final moisture content of 8 ± 2% was reached. The intensity of warping (twisting, bowing, cupping, crooking), superficial, internal, and end checks, residual stresses, drying rate, and moisture gradient of the dried woods were measured, and the results were evaluated according to the classification of the European Drying Group. The results showed a more homogeneous moisture profile, fewer occurrences of superficial checks, and an absence of internal checks when using the protective drying schedule due to low warping values compared with those for the non-protective drying schedule. From the point of view of energy efficiency, by saving 60 h of drying time, the non-protective schedule reduced electricity by 960 KWh and was therefore more profitable by $105.60 in this trial. Therefore, it seems that the protective drying schedule should be recommended as the optimum program for drying Turkish hazel lumber from the Kastamonu region at the commercial scale.